Pension Plan and Household Food Insecurity of Older Persons in Indonesia - Indrawan, Budi; Kharisma, Bayu; Remi, Sutyastie S. (Journal of Population and Social Studies [JPSS], 2023)
This study aims to determine the relationship between household food insecurity, old age security, and pension plans. It utilizes cross-sectional data from 97,797 pension households in the 2020 National Socioeconomic Survey (SUSENAS). A logistic regression model is applied to identify factors influencing household food insecurity as an indicator of poverty in pension households (aged 57 and older). The results reveal that most pension households experience varying degrees of food insecurity, with 25.45% lacking food security, 24.63% being vulnerable, and 18.54% experiencing food insecurity. Old age security (OAS) and pension plans effectively mitigate food insecurity, as they are significantly associated with food insecurity in pension households. Factors like low education levels among household heads, unemployed spouses, living in rental housing, older household heads, male household heads, married household heads, larger family sizes, and residing in rural areas positively correlate with household food insecurity. Special attention should be given to older pensioners living in rental houses, pensioners with low levels of education, those living in remote areas, and those with larger families. Government efforts to promote participation in OAS and pension plans offer short-term solutions while achieving educational equality represents a long-term goal.